PENERAPAN PERILAKU DISIPLIN SISWA KELAS V MELALUI PEMBELAJARAN BERBASIS RUTIN KELAS HARIAN DI SD NEGERI PANCA TUNGGAL - Siti lestari, Desy; Wahid Hasim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of daily class routine-based learning to enhance class V students' disciplinary behavior at SD Negeri Panca Tunggal. Research objectives include describing routine planning-implementation, transformation processes, and specific discipline changes such as punctuality and cooperation. A qualitative case study approach was employed, with data from observations, interviews, and documentation over 3 months, analyzed via reduction and triangulation. Findings reveal routines like morning assemblies and rotation duties boosted compliance from 25% to 85-95%, aligning with Skinner's behaviorism and Merdeka Curriculum. Significant behavioral shifts occurred in time discipline (35% violation reduction) and instruction adherence, recommending replication in rural elementary schools.